(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-150-159 Nowadays we can see a growing interest to the Russian language among Chinese citizens. The thing is that there are many relevant factors that may be the reasons for that, but the most vital is active collaboration development between Russia and China on the government level. These days Chinese students are learning Russian language when they come to Russia or being in China. On the one hand, a great number of students are aimed to come to Russia and learn the Russian language in the natural language environment. On the other hand, Chinese higher education establishments strive for inviting Russian teachers for their faculties to create favorable language environment, mastering the language out of Russian-speaking environment. It is of higher importance, that in Chinese higher education establishments are trying to create the most favorable conditions, fulfilling all the modern requirements, for learners of the Russian language. However, Russian teachers often face some difficulties. Teachers state that the biggest problem of these students is obtaining speaking skills, taking initiative in oral communication in Russian. The aim of this article is to observe and analyze problems of teaching Russian (its speaking aspect) in Chinese higher education establishments in the light of national personality traits. We also aim to represent some methods and recommendations to update the learning process. While teaching Russian in China a teacher from Russia has to create language environment, which must not contradict Chinese mindset, and encourage students to teach and think “as Russians do.” It is worth using pictures and different objects, such as a piece of chalk and mediatechnologies, giving modern and useful knowledge on country studies, going to a club or visiting a theatre, etc. To get the best results in a short period of time a teacher must respect his country and involve his students into language learning. Key words: methodology of teaching RFL, Russian as a foreign language, China, Chinese students, higher education establishments, methods of teaching, national character, oral speech, speaking